Efeito varietal e do espaçamento entre linhas no patossistema soja - Phakopsora pachyrhizi Sidow - Madalosso, Marcelo Gripa (2010)
The technical recommendation for the row spacing of soybean to be practiced in southern Brazil varies from 20 to 50 cm. This recommendation is wide, since climatic and physiological differences are at issue in choosing the distance between lines. The hight density of plants may provide different characteristics that favor the pathogenesis, reduce the penetration and coverage of fungicide, as well as affect the physiological plant expression. This study aimed to assess in two seasons, the response of soybean cultivars subjected to different row spacings and control programs under natural pressure of Phakopsora pachyrhizi Sidow. The work was carried out at a Phytus Research Institute | Research Division in the Itaara city, central region of Rio Grande do Sul in the crop 07/08 and 08/09. The main plots were composed of the row spacings of 40, 50 and 60 cm, the split plots correspond to the cultivars Asgrow 8000 RG and Asgrow 6001 RG and control programs were the split split plots. The fungicide used were the mixture (azoxystrobin + cyproconazole +) + adjuvant [(0.3) + 0.6 L of pc.ha-1].The reduction of row spacing allowed more conditions for the establishment and progress of the rust for the two cultivars. Thus, soybean row spacing 50 and 60 cm allowed the greatest range of applications. In the case of cultivars that allow high rate of progress of rust, depend on control programs that start at closing row spacing, require a third application of fungicide. The productivity of two cultivars was maximized with the row spacing of 60 cm, and the pods with two grains correspond to most contribute and are positioned in the middle of the plant. Thus, the correct construction of control program needs to know the suitable row spacing cultivar and the knowledge of the disease epidemiology.